The Book of Armagh: A codicological reassessment - Gillis, John (My University, 2021)
The Book of Armagh (Dublin, Trinity College, TCD MS 52) is an early ninth- century composite vellum manuscript from an Insular orbit. Its contents include a complete copy of the New Testament, along with documents relating to St Patrick and St Martin of Tours. The manuscript has been attributed to the scribe and artist Ferdomnach, whose name appears on its pages. One inscription records that the manuscript was produced for Torbach, who was Abbot of Armagh for just one year in 807. This colophon allows for an atypically accurate dating for its production. Two additional items have been historically associated with the Book of Armagh ; a fifteenth-century, highly decorated leather satchel and a pair of oak binding boards, considered to be the original boards of the manuscript. Expert examination of these boards thus far includes two studies, over twenty years apart, neither of which was published in detail. This paper intends to address the lack of codicological details relating to the boards and examine the possible scenarios as to their intended original function as they relate to the manuscript.
PUBLISHED
Keywords: Manuscript, Book and Print Cultures; Irish Manuscripts; Medieval manuscripts; codicology; manuscript studies